2003
DOI: 10.1002/zaac.200300253
|View full text |Cite
|
Sign up to set email alerts
|

Ein‐ und zweikernige Kupfer(I)‐ und Silber(I)‐Phosphan‐Komplexe mit β‐Diketonato‐Teilstrukturen

Abstract: Die Reaktion von [(η2‐Me3SiC≡CSiMe3)CuBr]2 (1) mit zwei Äquivalenten an [M(O∩O)] [M = Na, Ag; O∩O = Acetylacetonat, acac, 2a/ 3a; = 1, 1, 1, 5, 5, 5‐Hexafluoroacetylacetonat, hfac, 2b/ 3b; = 2, 2, 6, 6‐Tetramethyl‐3, 5‐heptandionat, tehe, 2c/ 3c; = 1, 3‐Diphenyl‐1, 3‐propandionat, dipa, 2d/ 3d; = 2‐Methyl‐4‐pyronat, mepy, 2e/ 3e; = Troponolat, trop, 2f/ 3f) führt zu [(η2‐Me3SiC≡CSiMe3)Cu(O∩O)] (4a, acac; 4b, hfac; 4c, tehe; 4d, dipa; 4e, mepy; 4f, trop), welche durch Umsetzung mit PR3 (R = C6H4CH2NMe2‐2)3 (5) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Moreover, the [L 2 Cu 6 ] core of 3 in the solid state features a cis arrangement of the two tacn units of each ligand strand L – as was also observed for 2 H . The CC stretch of the bound phenylacetylide in 3 was found at 1852 cm –1 , i.e., significantly lower than that in free HCCPh (2119 cm –1 ), in accordance with the side-on coordination to a Cu­(I) ion and substantial π-backbonding. …”
Section: Resultsmentioning
confidence: 80%
“…Moreover, the [L 2 Cu 6 ] core of 3 in the solid state features a cis arrangement of the two tacn units of each ligand strand L – as was also observed for 2 H . The CC stretch of the bound phenylacetylide in 3 was found at 1852 cm –1 , i.e., significantly lower than that in free HCCPh (2119 cm –1 ), in accordance with the side-on coordination to a Cu­(I) ion and substantial π-backbonding. …”
Section: Resultsmentioning
confidence: 80%
“…Elemental analysis of 19 is in good agreement with the proposed composition. The 31 P{ 1 H} NMR spectrum of 19 is indicative of the coordination of the diphenylphosphanyl group to copper(I) because a typical chemical shift from δ = –18.3 ( 5 ) to –14.9 ppm ( 19 ) is found 26. A broad signal is observed that is attributed to the two isotopes of copper ( 63 Cu, 65 Cu) 27.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, they attained great interest in, for example, the deposition of metal or metal oxide thin layers by applying diverse deposition techniques, including CVD (=chemical vapor deposition) [ 1 , 11 , 12 , 13 , 14 ], ALD (=atomic layer deposition) [ 15 , 16 , 17 , 18 , 19 ], and spin-coating [ 20 , 21 , 22 ]. In addition, they received great interest in the synthesis of (hetero)multimetallic complexes [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ] as catalysts in organic synthesis [ 30 , 31 , 32 ] and as anticancer drugs (especially copper and rhodium β-diketonates) [ 33 , 34 , 35 ]. Recently, they gained topical attention in the study of electron transfer processes, when, for example, redox-active groups such as ferrocenyls are present, i.e., in zirconium, hafnium, copper(I), copper(II), manganese, ruthenium, rhodium(I), and aluminum β-diketonate complexes [ 36 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%